Pengembangan dan Validasi Soal Berpikir Kritis Berbasis Etnomatematika pada Bangunan Tabut Bansal Bengkulu - Ayu Tania Riski Putri; Adi Asmara; Nyayu Masyita Ariani (FKIP Universitas Mataram, 2026)
This research aims to develop ethnomathematics-based critical thinking skills tasks within the context of the Tabut Bengkulu structure that meet the criteria for validity. The urgency of this study is driven by the significance of 21st century critical thinking skills, which demand contextual assessment innovations for students. Utilizing the Research and Development (R&D) method with the Tessmer’s formative evaluation model as adapted by Zulkardi, this study encompasses stages from preliminary research to formative evaluation (self-evaluation, expert review, and one-to-one). The designed instruments consist of five essay items integrating Facione's critical thinking indicators with the Bengkulu curtural context of Tabut Bansal. The results indicate that prototype 1 was declared valid in terms of content, construct, and language by the three validators. One-to-one trials with junior high school students also demonstrated that the tasks possess good readability and are capable of stimulating student’s cognitive activity in solving contextual mathematical problems. This research produced prototype 2, comprising five essay items designed to train and measure mathematical critical thinking skills in junior high school.